The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2478/johr-2014-0030
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation Of Nacl Stress In Summer Squash ‘Eskandrani’ By Foliar Application Of Salicylic Acid

Abstract: The experiment was performed to assess the possibility of overcoming NaCl salinity stress by foliar sprays of summer squash ‘Eskandrani’ with salicylic acid (SA) at the concentration of 10-6 M. NaCl treatment caused reduction of shoot fresh weight, leaf number per plant, fruit yield, concentrations of potassium in aerial parts, and the concentration of chlorophyll in leaves. Plants grown under salt stress conditions had higher shoot sodium concentrations than plants untreated with NaCl. Foliar application of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…Our results showed that exogenous SA had a positive effect on muskmelon growth and tempted salinity stress for it. Exogenous SA significantly improved all the vegetative growth attributes both in normal and saline conditions and these findings are in Ibrarullah et al accordance of previous reports (Elwan and EL-Shatoury, 2014;Noreen and Ashraf, 2008), who acquired greater biomass for sunflower and cabbage plants both in saline and non-saline conditions when treated with SA. Bayat et al (2012) described that exogenous SA increased shoot and root dry weight, leaf areas and plant heights of calendula under salinity stress conditions.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Our results showed that exogenous SA had a positive effect on muskmelon growth and tempted salinity stress for it. Exogenous SA significantly improved all the vegetative growth attributes both in normal and saline conditions and these findings are in Ibrarullah et al accordance of previous reports (Elwan and EL-Shatoury, 2014;Noreen and Ashraf, 2008), who acquired greater biomass for sunflower and cabbage plants both in saline and non-saline conditions when treated with SA. Bayat et al (2012) described that exogenous SA increased shoot and root dry weight, leaf areas and plant heights of calendula under salinity stress conditions.…”
Section: Resultssupporting
confidence: 88%
“…Numerous studies describe the productive role of SA in plants under salt stress conditions (Yadu et al, 2017;Tufail et al, 2013). Exogenous SA has the feature to reduce toxic ions (Na + ) accretion in shoot and leaf and increase ratio of beneficial ions such as K + and Ca 2+ in saline conditions (Elwan and El-Shatoury, 2014). In addition to this, SA fastens the uptake of other plant beneficial elements such as Mn, Ca, Cu, Fe, P and Zn and thereby reduces oxidative stress (Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, seedlings were irrigated with ddH 2 O containing 0 (control), 50, 100 and 150 mM NaCl. While half of the plants were sprayed with 3 mM AsA (Elwan et al, 2012;Ergin et al, 2014) every three days for 2 weeks (5 applications) in order to investigate whether AsA was effective on salt tolerance of the genotypes, the other half were used as control plants. The amount of water to be given was determined by the pot tensiometer (Irrometer, Co. Riverside, Calif, USA).…”
Section: Plant Materials and Experimental Practicesmentioning
confidence: 99%
“…In addition, exogenous application of salicylic acid induces the antioxidant enzymes activity and subsequently augments plant resistance to NaCl toxicity (He and Zhu 2008). The ameliorative effects of foliar application of salicylic acid have been reported in inducing salt tolerance in some cucurbits such as cucumber (Yildirim et al, 2008, Dong et al, 2011and Youssef et al, 2018, summer squash (Elwan and El-Shatoury 2014), melon (Nasrabadi and Saberali 2020) and watermelon (Ayyub et al, 2015 andRibeiro et al, 2020).…”
Section: Introductionmentioning
confidence: 99%